The Effect of Hydro-Alcoholic Garlic Extract on Testis Weight and Spermatogenesis in Mature Male Rats under Chemotherapy with Cyclophosphamide - Marzie Mirfard; Habibolah Johari; Mokhtar Mokhtari; Vahid Hematkhah; Hoshang Jamali; Ghadre Allahverdi (Fasa University of Medical Sciences, 2011)
Background & Objectives: Cyclophosphamide (with the brand name of Endoxana) is an anti-cancer drug used in chemotherapy. The side effects of this drug include anoretic, nausea, decrease in genital gland function, creating amenorrhea, azoospermia and oligospermia. Garlic has been used throughout history as a medicinal drug and a beneficial spice in cooking. The beneficial effects of garlic which have been studied are its anti-oxidant, antibacterial, anti- atherosclerosis, anti-blood platelet effects as well as its role in reducing blood glucose and fat. Garlic has many compounds mostly contain a sulfuric content such as Di-alkyl Di-sulfide (Alicin), Di alyl Di sulfide (DAS), that caused antioxidant and protective properties. Materials & Methods: Cyclophosphamide and garlic extract were given to 56 rats for a period of 28 days. The rats were weighted and after anesthesia, their testis was taken out and tissue dissections were obtained, Student t-test was applied for the statistical analysis. Results: The results show that cyclophosphamide alone leads to a reduction in body and testis weight, and spermatogenesis compared to the control group. In the group that used cyclophosphamide along with garlic extract, as the dose of extract increased, the body and testis weight and spermatogenesis increased in the rats. Conclusion: It seems, the existing compounds in garlic extract can control active metabolites caused by cyclophosphamide and the destructive effect of this drug. Prescribing garlic extract along with cyclophosphamide can possibly be beneficial and effective due to the anti-oxidant characteristics of garlic and also its effect on reducing harmful metabolites.